Principle Study of a Semi-active Inerter Featuring Magnetorheological Effect - Zhong, Wei-Min; Bai, Xian-Xu; Tang, Chao; Zhu, An-Ding (Frontiers in Materials, 2019)
Inerters are a two-terminal mass element, and the forces applied at their two terminals are proportional to the relative acceleration between the two terminals. The volume and weight of inerters are much smaller than those of any conventional mass element providing a same generated force, which is beneficial to engineering applications. The inerter in mechanical system is completely corresponding to the capacitor in electrical system, which makes it more convenient to do related investigations based on mechanical-electrical analogies. A semi-active inerter (SAI) featuring magnetorheological (MR) effect with tunable inertance is proposed, designed and investigated to enhance the performance of the passive inerters. The proposed SAI consists of a flywheel, a flywheel housing, a ball screw, a connection sleeve, bearings, upper and lower covers, excitation coils and MR fluid. MR fluid fulfilled in the flywheel housing of the SAI is energized by the excitation coils with applied current, and correspondingly the mechanical characteristics of the SAI is tunable via the applied current. The mathematical model and the mechanical performance of the SAI is established and tested, respectively. The nonlinearity of the experimental results is analyzed and the nonlinear model of the SAI is further established. The preliminary principle verification of the continuous adjustment of the equivalent inertance of the SAI is conducted using the nonlinear model. Moreover, a compensator is proposed to address the problem of the phase difference between the controllable force and the real output force of the SAI, and continuous inertance adjustment of the SAI with a compensator is realized and analyzed.